2014
DOI: 10.1007/s40279-014-0158-x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Interval Training vs. Moderate Continuous Training in Coronary Artery Disease Patients: A Systematic Review and Meta-Analysis

Abstract: In CAD patients with preserved and/or reduced LVEF, AIT is superior to MCT for improving peakVO2, while MCT seems to be more effective in reducing body weight. However, large, well-designed, randomized controlled trials are warranted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
82
0
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 54 publications
14
82
0
21
Order By: Relevance
“…An increase in peak VO 2 after exercise training is well documented, [29][30][31][32] and our group already demonstrated that the OUES shows a similar response to training in CAD patients. 10 Furthermore, previous research showed that cardiac rehabilitation reduces the risk for future fatal and non-fatal events in patients with CAD.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…An increase in peak VO 2 after exercise training is well documented, [29][30][31][32] and our group already demonstrated that the OUES shows a similar response to training in CAD patients. 10 Furthermore, previous research showed that cardiac rehabilitation reduces the risk for future fatal and non-fatal events in patients with CAD.…”
Section: Discussionsupporting
confidence: 62%
“…18,31,33,35,38 Thus, an increase in exercise capacity is related to a reduction of all-cause and CV events. 22,32,34,36,39 Regarding submaximal measures of exercise capacity, one study in patients with CAD found an increase in exercise capacity, expressed in metabolic equivalent of the task, of 32% after a 12-week cardiac rehabilitation program. They calculated the Duke prognostic risk score, which is a validated risk score that predicts 5-year CV mortality using data from an exercise tolerance test, and found that the risk for CV mortality decreased by 33% among their study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of HIIT is to repeatedly stress the physiological system (7). In 2010-2014, several reviews and meta-analyses of HIIT for CAD and CHF were published (8)(9)(10)(11)(12)(13)(14), reflecting its increasing interest in the field of cardiac rehabilitation. One of these studies (11) involving more than 260 patients, the superiority of HIIT in patients with CAD was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CAD with preserved or reduced LVEF, HIIAT showed to be superior to moderate MCT to improve VO 2peak , which is closely related to long-term survival in cardiac patients [26].…”
Section: Beneits Of Cardiac Rehabilitation In Cardiac Diseases: Coronmentioning
confidence: 89%